Advances in ground improvement using waste materials for transportation infrastructure. Issue 1 (23rd February 2022) - Indraratna, Buddhima; Qi, Yujie; Tawk, Miriam; Heitor, Ana; Rujikiatkamjorn, Cholachat; Navaratnarajah, Sinniah K.
Abstract : Recycling waste materials for transport infrastructure such as coal wash (CW), steel furnace slag (SFS), fly ash (FA) and recycled tyre products is an efficient way of minimising the stockpiles of waste materials while offering significant economic and environmental benefits, as well as improving the stability and longevity of infrastructure foundations. This paper presents some of the most recent state-of-the-art studies undertaken at the University of Wollongong, Australia on the use of waste materials such as ( a ) CW-based granular mixtures (i.e. SFS + CW, CW + FA) for port reclamation and road base/subbase and ( b ) using recycled tyre products (i.e. rubber crumbs, tyre cell, under-sleeper pads and under-ballast mats) to increase track stability and reduce ballast degradation. Typical methods of applying these waste materials for different infrastructure conditions are described and the results of comprehensive laboratory and field tests are presented and discussed.